Diethyl (cyanofluoromethyl)phosphonate: Application in catalytic enantioselective Michael additions. (3rd June 2017) - Jászay, Zsuzsa; Tódor, István; Rapi, Zsolt; Bakó, Péter; Petneházy, Imre; Tőke, László
GRAPHICAL ABSTRACT: ABSTRACT: Three types of chiral catalysts: a chincona-based squaramide, TADDOL and a group of sugar-based crown ethers were applied to the asymmetric Michael addition of diethyl (cyanofluoromethyl)phosphonate to diverse Michael acceptors. Two of the crown ether catalysts resulted in high yields and enantioselectivities with trans -β-nitostyrene as in case of the chincona-based squaramide catalyst the yield was low with high enantioselectivity. TADDOL proved to be active, but less selective in the Michael addition.